Social Psychological Foundations of Health and Illness 2003
DOI: 10.1002/9780470753552.ch8
|View full text |Cite
|
Sign up to set email alerts
|

Common Sense Models of Illness: Implications for Symptom Perception and Health‐Related Behaviors

Abstract: Psychological factors influencing self-assessments of health: Toward an understanding of the mechanisms underlying how people rate their own health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 93 publications
4
44
0
3
Order By: Relevance
“…Finally, some studies have not demonstrated a significant association between negative affect and symptom reporting (Diefenbach, Leventhal, Leventhal, & Patrick-Miller, 1996). In attempting to integrate these discrepant findings, Martin et al (2003) conclude that the key to understanding the role of negative affect in health care seeking is specifying the context in which symptom reporting is being examined.…”
Section: Maternal Health Care Seeking For Children Within the Common mentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, some studies have not demonstrated a significant association between negative affect and symptom reporting (Diefenbach, Leventhal, Leventhal, & Patrick-Miller, 1996). In attempting to integrate these discrepant findings, Martin et al (2003) conclude that the key to understanding the role of negative affect in health care seeking is specifying the context in which symptom reporting is being examined.…”
Section: Maternal Health Care Seeking For Children Within the Common mentioning
confidence: 99%
“…The common sense model of health and illness behaviors (Martin, Rothrock, Leventhal, & Leventhal, 2003;Meyer, Leventhal, & Gutmann, 1985) may constitute a framework to study the role of mothers in determining pediatric health care use. In the common sense model, the person's cognitive representations of and affective reactions to bodily states influence health care decision-making.…”
Section: Maternal Health Care Seeking For Children Within the Common mentioning
confidence: 99%
See 3 more Smart Citations